Nghiên cứu so sánh cấu trúc, độ bền của cluster silic pha tạp SinM (M là Sc, Y; n = 1-10) bằng phương pháp hóa học lượng tử - Cường, Nguyễn Quốc; Phi, Nguyễn Duy; Ngân, Vũ Thị; Hùng, Nguyễn Phi; Trung, Nguyễn Tiến (Vietnam Journal of Chemistry, 2016)
Geometrical structures and stabilities of the doped SinM (M = Sc, Y; n = 1-10) clusters were thoroughly investigated using density functional theory. The geometrical optimizations and harmonic frequency calculations were performed at the B3P86/DGDZVP level of theory. We found that the doped clusters SinSc, SinY are less symmetrical than the pure Sin+1 clusters. The ground states of SinM with n = 2-10 favor the low-spin state (doublet). Analysis of the growth mechanism found that the substitution rule is strictly obeyed as n £ 6 while it is not true for the rest. As n > 6, the two dopants modified the structures of silicon clusters in various ways leading to many low-lying isomers. The metal atoms can be substituted to either a pentagonal bipyramidal structure or a trigonal prism or even formed a new structure. Analysis of energetic parameters including average binding energy, fragmentation energy, second-order difference of energy, HOMO-LUMO gap indicates that the stability of doped clusters are in general lower than the corresponding pure Si clusters. Keywords. Sc-doped Si cluster, Y-doped Si cluster, B3P86, stability of cluster